Safety Verification of Uncertain Max-Plus-Linear Systems - Aditya Putra Pratama; Subchan Subchan; Dieky Adzkiya ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2018)
In this work, we discussed the verification of autonomous uncertain Max-Plus-Linear (uncertain MPL) systems with respect to safety property by using the reachability analysis approach. More precisely, given an uncertain MPL system, a nonempty set of initial conditions, a time horizon and an unsafe set, we want to determine whether the state can reach the unsafe set within the given time horizon. If the unsafe set is reachable, then the system is not safe. Otherwise, the system is safe. Our approach uses the piecewise affine representation of MPL systems to compute the reachable sets exactly.